(untitled) (Baghdad Science Journal, 2020)
This study investigated the prevalence of quinolones resistance proteins encoding genes (qnr genes) and co-resistance for fluoroquinolones and β-lactams among clinical isolates of Klebsiella pneumoniae. Out of 150 clinical samples, 50 isolates of K. pneumoniae were identified according to morphological and biochemical properties. These isolates were collected from different clinical samples, including 15 (30%) urine, 12 (24%) blood, 9 (18%) sputum, 9 (18%) wound, and 5 (10%) burn. The minimum inhibitory concentrations (MICs) assay revealed that 15 (30%) of isolates were resistant to ciprofloxacin (≥4µg/ml), 11 (22%) of isolates were resistant to levofloxacin (≥8 µg/ml), 21 (42%) of isolates were resistant to ertapenem (≥8 µg/ml), 18 (36%) of isolates were resistant to imipenem (4- ≥16µg/ml), 43 (86%) of isolates were resistant to ceftriaxone (4- ≥64 µg/ml), 42 (84%) of isolates were resistant to ceftazidime (16-64 µg/ml), and 40 (80%) of isolates were resistant to cefepime (4- ≥16µg/ml). The results revealed that all fluoroquinolone resistant K. pneumoniae isolates were resistant for β-lactams that used in this study. Genotypic detection of qnr genes revealed that qnrS and qnrB were found in 38 (76%) and 18 (36%) of K. pneumoniae isolates, respectively. On the other hand, qnrA, qnrC, and qnrD were not found among K. pneumoniae isolates. DNA sequencing of qnrB gene revealed that the presence of silent and missense mutations that may have led to increase the resistance values of MICs for ciprofloxacin and levofloxacin. These variants were registered in NCBI at the accession numbers LC373260 and LC381730. The phylogenetic tree of qnrB variants showed a significant deviation of these variants from K. pneumoniae species. The spread of qnr genes among clinical isolates of K. pneumoniae and high association observed between resistance to fluoroquinolones and β-lactams have led to a major threat to public health through development of MDR K. pneumoniae.